Retail reform: profitable shopping-mall revitalization that reflects changes in projected retail, residential and mixed-use markets - Studer, Brian (Kansas State University, 2022)
The discussion of what is next for underperforming shopping malls has been a consistent issue in the realm of urban redevelopment and consumerism over the past decade. While the future of retail shopping and the effects of online shopping has been widely explored in recent years, less attention has been paid to the potential monetary and community value that these underutilized shopping malls offer. This project and report address the issue by examining the efficiency of the social, environmental, and financial aspects of shopping mall redevelopment through a mixed-use approach. More specifically, this report investigates how Mayfair Mall, an underperforming mall located in Wauwatosa, Wisconsin, can be revitalized to potentially increase the overall profitability of the asset while reinvigorating the community with new amenities and experiences. This specific mall was not only chosen due to personal familiarity, but also from the site’s typical characteristics and context of a traditional shopping mall, such as building organization, community size, and the overall economic health of the community. This project used a mixed method approach to collect data from invested stakeholders and participants of the Mayfair Mall community to better communicate to the audience about the potential for this undervalued site. The tools used to collect data included a precedent analysis, case studies, and interviews, which informed three distinct projective designs based on current redevelopment strategies. These findings offer some insight and recommendations towards the future development strategies of underperforming malls around the country, while contributing to the existing body of literature through the identification and influence of projected retail, residential, and industrial/office markets. The broader outcome of this report highlights the role of real estate developers, urban planners, and landscape architects in redeveloping underperforming shopping malls into a central community asset that aligns with current development trends.
Keywords: Shopping mall; Mixed-use; Retrofit; Retail; Redevelopment; Mayfair mall